Red Blood Cell Parameters and Their Correlation with Glycemic Control Among Type 2 Diabetics - Muqadus, Momina; Amer, Wasim; Shahid, Seemab; Ahmed, Syed Noman; Ahmed, Zahoola; Usman, Muhammad (Indus Journal of Bioscience Research, 2025)
Objective: “To determine the correlation of red blood cell parameters with glycemic control among type 2 diabetics”. Study design: Cross-Sectional Study. Study place and duration: Department of Medicine, Ghurki Trust Teaching Hospital, Lahore for a duration of 3 months from 17 January 2025 to 20 April 2025. Methodology: Patients were recruited from medical OPD and blood sample was taken for assessment of RBC parameters and fasting blood glucose level. Reports were assessed and levels were recorded. All this information was recorded in proforma and analyzed in SPSSv.25. Spearman’s correlation coefficient was calculated to measure correlation between glycemic control and hematological parameters. Results: In this study, the mean age of diabetics was 49.95 ± 12.28 years. There were 148 (53.2%) male diabetics and 130 (46.8%) female diabetics. Hematological parameters were observed as mean fasting blood glucose level of diabetics was 153.24 ± 25.31 mg/dl, mean red blood cell count was 5.32 ± 0.56 cells/µL, mean hematocrit level was 39.02 ± 10.47% and mean hemoglobin level was 14.08 ± 4.06 g/dl. Out of 278 diabetics, 145 (52.16%) had good glycemic control while 133 (47.84%) had poor glycemic control. It has been observed that the glycemic control had negative weak relationship with red blood cell count i.e. r = -0.343 (p-value <0.05). Similarly, glycemic control had negative weak relationship with hematocrit level i.e. r = -0.484 (p-value <0.05). But the relationship between glycemic control and hemoglobin level was very weak, although positive i.e. r = 0.065 (p-value >0.05). Conclusion: It is concluded that hematological parameters have negative relationship with glycemic control. As the glycemic level will increase, hematological parameters will decrease, leading to deterioration of health of diabetic patient.